2019
DOI: 10.1177/0018578718823733
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in Hospital Pharmacy Practice in Lebanon

Abstract: Objectives: For decades, the role of hospital pharmacists has been instrumental in elevating pharmacy practice worldwide. Recently, the Hospital Pharmacy Section of the International Pharmaceutical Federation (FIP), the European Association of Hospital Pharmacists (EAHP), and the American Society of Health-System Pharmacists (ASHP) updated their statements about the future role and responsibilities of the pharmacy executive in hospitals and health systems. A series of surveys were conducted around the globe to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The added value of a pharmacist in multidisciplinary intra- and inter-professional healthcare teams was highlighted in several studies ( Bond and Raehl, 2007 , Leary et al, 2019 , Zhai et al, 2016 ). However, findings from the present study were similar to other studies in the region that showed the limited participation of pharmacists in multidisciplinary healthcare services ( Chamoun et al, 2020 ). Therefore, there is a need to develop and implement structured and evidence-based strategies, systems, and protocols for integrated professional services and to advocate for pharmacists as active members in these services.…”
Section: Discussionsupporting
confidence: 91%
“…The added value of a pharmacist in multidisciplinary intra- and inter-professional healthcare teams was highlighted in several studies ( Bond and Raehl, 2007 , Leary et al, 2019 , Zhai et al, 2016 ). However, findings from the present study were similar to other studies in the region that showed the limited participation of pharmacists in multidisciplinary healthcare services ( Chamoun et al, 2020 ). Therefore, there is a need to develop and implement structured and evidence-based strategies, systems, and protocols for integrated professional services and to advocate for pharmacists as active members in these services.…”
Section: Discussionsupporting
confidence: 91%
“…32 Pharmacists have a very comprehensive role within the hospital, performing from administrative activities to clinical services. 33 Therefore, they must be involved with all aspects of medicines use and be accessible as a point of contact for patients and health care providers. 34 As a consequence, it is more than expected that they would be on the frontline against COVID-19 pandemic and reporting on their successful experiences.…”
Section: General View Of the Studiesmentioning
confidence: 99%
“…Some of these recommendations might be appropriate to other healthcare settings or help in assessing the extent and quality of pharmacy services. Several researchers have used these standards to evaluate hospital pharmacy practices in Iran, Saudi Arabia, Lebanon, and Spain, respectively [26][27][28][29]. The questionnaire used in this study was modified from the original ASPH standards.…”
Section: Data Collection Toolmentioning
confidence: 99%